Naegleria fowleri, the Causative Agent of Primary Amoebic Meningoencephalitis : Naegleria fowleri, the Causative Agent of Primary Amoebic Meningoencephalitis - Mushtaq, Sadaf; Shinwari, Zabta Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Primary amoebic meningoencephalitis (PAM) is a fatal disease of central nervous system caused by free living amoebae, Naegleria fowleri. The disease is associated with exposure to contaminated water followed by brain tissue damage and death. Diagnosis of the disease is difficult due to similarity with bacterial meningoencephalitis. However, wet mount of cerebrospinal fluid (CSF), biochemical and various molecular techniques help in timely diagnosis of the disease. Treatment regimen includes high dose of amphotericin B alone or in combination with miconazole, sulfisoxazole and rifampin. However, several antibacterial and antifungal drugs have also shown potential antiamoebic activity. Exposure to N. fowleri can be prevented by chlorination of swimming pools and monitoring of recreational water bodies by the local authorities. This review provides an overview of the current knowledge about Naegleria fowleri as a disease causing pathogen along with recent diagnostic and treatment strategies to combat primary amoebic meningoencephalitis.